2022
DOI: 10.3390/s22218310
|View full text |Cite
|
Sign up to set email alerts
|

Electric Impedance Spectroscopy in Trees Condition Analysis: Theory and Experiment

Abstract: Electric impedance spectroscopy is an alternative technology to existing methods that shows promising results in the agro-food industry and plant physiology research. For example, this technology makes it possible to monitor the condition of plants, even in the early stages of development, and to control the quality of finished products. However, the use of electric impedance spectroscopy is often associated with the need to organize special laboratory conditions for measurements. Our aim is to extract informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This enhancement contributes to a faster accumulation of plant biomass. Furthermore, the impedance spectroscopy [113,114] revealed that plasma treatment contributes to the formation of a more advanced vascular system within the grafting area.…”
Section: Dielectric Barrier Dischargementioning
confidence: 99%
“…This enhancement contributes to a faster accumulation of plant biomass. Furthermore, the impedance spectroscopy [113,114] revealed that plasma treatment contributes to the formation of a more advanced vascular system within the grafting area.…”
Section: Dielectric Barrier Dischargementioning
confidence: 99%
“…The rooting potential of shoot cuttings was investigated by Mancuso (1999) through double-DCE equivalent electrical circuit models. Recently, Astashev et al (2022) also developed a sensor and model to conduct in situ EIS measurements evaluating the physiological condition of trees. Branch length, tree health, and effects of drying and grafting were all impedimetrically evaluated.…”
Section: Overview Of Plant Eis Applicationsmentioning
confidence: 99%
“…The "CAPKO" source in the DBD plasma generation mode was studied in relation to the effect on the quality of growth of pear and cherry after grafting [40][41][42]. Rootstock and scion cuts were treated with DBD CAP during grafting.…”
Section: Introductionmentioning
confidence: 99%